A Preliminary Computational Investigation Into the Flow of PEG in Rat Myocardial Tissue for Regenerative Therapy - Ngoepe, Malebogo; Passos, Andreas; Balabani, Stavroula; King, Jesse; Lynn, Anastasia; Moodley, Jasanth; Swanson, Liam; Bezuidenhout, Deon; Davies, Neil H.; Franz, Thomas (Frontiers in Cardiovascular Medicine, 2019)
Myocardial infarction (MI), a type of cardiovascular disease, affects a significant proportion of people around the world. Traditionally, non-communicable chronic diseases were largely associated with ageing populations in higher income countries. It is now evident that low- to middle-income countries are also affected and in these settings, younger individuals are at high risk. Currently, interventions for MI prolong the time to heart failure. Regenerative medicine and stem cell therapy have the potential to mitigate the effects of MI and to significantly improve the quality of life for patients. The main drawback with these therapies is that many of the injected cells are lost due to the vigorous motion of the heart. Great effort has been directed towards the development of scaffolds which can be injected alongside stem cells, in an attempt to improve retention and cell engraftment. In some cases, the scaffold alone has been seen to improve heart function. This study focuses on polyethylene glycol (PEG) solution, the basis of a synthetic hydrogel injected into the heart to improve left ventricular function following MI. Many studies in literature characterise PEG as a Newtonian fluid within a specified shear rate range, on the macroscale. The aim of the study is to characterise the flow of PEG 20000 on the microscale, where the behaviour is likely to deviate from macroscale flow patterns. Micro particle image velocimetry (μPIV) is used to observe flow behaviour in microchannels, representing the gaps in myocardial tissue. The fluid exhibits non-Newtonian, shear-thinning behaviour at this scale. Idealised two-dimensional and three-dimensional computational fluid dynamics (CFD) models of PEG flow in microchannels are then developed and validated using the μPIV study. The validated computational model is applied to a realistic, microscopy-derived myocardial tissue model. From the realistic tissue reconstruction, it is evident that the injection site plays an important role in the distribution of PEG, and therefore, in the retention of material.